Prediksi Promosi Jabatan Karyawan JNE Pematangsiantar Dengan Algoritma C4.5 - Rizki Ananda; Sumarno Sumarno; Indra Gunawan (Universitas Budi Darma, 2022)
This study predicts employee promotions using employee data from PT. JNE Pematangsiantar. The purpose of this research is to obtain a rule model in classifying predictions of promotions in the company. By knowing this prediction, decision makers can choose employees who will be promoted according to the rules that apply in the company. The method used in this research is Data Mining Algorithm C4.5, with employee data used as many as 20 employees. The variables used in this study include: Job Knowledge, Competence, Teamwork, Communication and Job Quality. The results of the study obtained 9 rules or rule models for this prediction classification with 5 rules with the final result being Promoted and 4 rules with the final result not being Promoted. With an accuracy rate of 71.43% and a classification error of 28.57%